Contribution of SAARC Countries to the Directory of Open Access Journals - Singh, Nirmal (Journal of Information and Knowledge, 2014)
The implementation of Information and Communication Technologies (ICTs) has revolutionised the information availability, accessibility and utilization. The Open Access movement is one of the greatest accomplishments of ICTs. It takes information to the doorsteps of the users without any charges and provides more visibility to the information generators. The Directory of Open Access Journals (DOAJ) has added a new chapter to the open access literature. Having its origin in 2002 with 30 journals, the Directory provides access to nearly 9500 journals in various disciplines. The South Asian Association for Regional Cooperation (SAARC) countries have contributed 732 journals in different subjects to DOAJ up to 11.06.2013. The present paper evaluates the contribution of SAARC nations to DOAJ. It is concluded that India and Pakistan are the dominant contributors to DOAJ among SAARC countries.